2010
DOI: 10.1111/j.1440-1797.2009.01257.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on dialysis patients after total parathyroidectomy without autoimplant

Abstract: In the studied series of total parathyroidectomy without autoimplant, adynamic bone disease occurred in three out of seven repeat bone biopsies while improvement occurred in the rest. Bone mineral density was much improved and there was no fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
6
1
1
Order By: Relevance
“…We observed a non-significant elevation of AP from 131 ± 19 to 147 ± 22 U/L in the perioperative period. In contrast to our findings, Chan et al [28] observed a perioperative decrease in AP among 13 patients who underwent total PTX without autotransplantation.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…We observed a non-significant elevation of AP from 131 ± 19 to 147 ± 22 U/L in the perioperative period. In contrast to our findings, Chan et al [28] observed a perioperative decrease in AP among 13 patients who underwent total PTX without autotransplantation.…”
Section: Discussioncontrasting
confidence: 54%
“…Bone pain is one of the main symptoms of renal osteopathy in patients with sHPT [28, 57]. In a retrospective study by Low et al [57], a perioperative reduction of bone pain, decreasing from 65 to 3.5%, was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of operative exploration for supernumerary glands may become less controversial with widespread utilization of the intraoperative PTH assay as an adjunct in guiding the completeness of resection. The utilization of intraoperative PTH monitoring may become a useful adjunct for assuring that the patient has undergone an adequate parathyroidectomy in sHPT [22-26]. Patients whose PTH level dropped under 400 ng/L by the removal of parathyroid gland, sHPT could be controlled by medical treatment after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…chan с соавторами из 13 гемодиализных пациентов, которым была выполнена тотальная паратиреоидэктомия по поводу вторичного гиперпаратиреоза, ни у одного из них не было выявлено переломов кости в средние сроки наблюдения 37,7 мес. [25]. В нашем исследовании рассчитан относительный риск развития осложнений с 95% ДИ при повышении уровня ПТГ и снижении витамина D 3 в сыворотке крови.…”
Section: рис 3 алгоритм периоперационного ведения пациентов получаunclassified